Implementing the hidden curriculum for biomedical graduate research trainees: leveraging qualitative data and student affairs personnel to develop soft skills - Ragland, Debra A.; Lowry, Augustus J.; Nardone-White, Dasean T.; Frierson, Johnna M. (Frontiers in Education, 2024)
Biomedical graduate research trainees are increasingly pursuing careers beyond academia in response to limited academic positions relative to the trainee population. Biomedical research training must therefore evolve alongside the shifting career landscape by circumventing a “hidden curriculum” to help trainees develop skills complementary to existing graduate training. Here, we describe an approach to implement “soft skills” training for a diverse population of biomedical graduate research trainees from the Duke University BioCoRE program. Qualitative data from the BioCoRE annual program survey revealed that trainees felt they were not meeting crucial benchmarks in areas often absent from graduate training. Responses to open-ended survey questions overwhelmingly focused on “soft skills,” including communication, conflict resolution, and time management. Using these themes as a guide, the BioCoRE Program Director and graduate student-led Professional Development Committee collaborated to design a monthly workshop series, enlisting support from human resources personnel, undergraduate student affairs offices, and senior graduate trainees with relevant expertise. The year-long workshop series covered a range of topics: personal branding, science communication, scientific storytelling, conflict resolution, time management, and job market preparation. Based on survey data, the inaugural series was well-received and cited as highly effective by attendees. Survey dissemination and analysis will continue in subsequent years to address new topics and anticipate emerging themes in the shifting career development landscape. Implementation of this workshop series demonstrates the ability of graduate programs to enhance trainee soft skills by leveraging the expertise of internal and local professional personnel.